Practical approach for reduction of fuel consumption on earthwork highway machineries [electronic resource] - Nurizan Ab. Rahman, 1990-; Rozana Zakaria (2013)
Thesis (Sarjana Kejuruteraan (Awam - Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2013